2017
DOI: 10.1080/09546634.2017.1329514
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in topical field treatment of actinic keratosis in Swedish and Danish patients

Abstract: Topical treatments in dermatology can be long, complex and lead to nonadherence and nonpersistence to prescribed treatment. Clinical efficacy observed in randomized clinical trials (RCT) may therefore be reduced in real-world clinical practice. The objective of this study was to analyze patient-reported treatment adherence, treatment satisfaction and health-related quality of life (HRQoL) with topical treatments of actinic keratosis (AK) in routine clinical practice in Denmark and Sweden. Adult patients prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…The TSQM‐9 is a reliable instrument to assess patients' satisfaction with treatment. It has been used to assess the treatment satisfaction in various diseases such as pulmonary arterial hypertension, multiple sclerosis, psoriasis vulgaris, diabetes mellitus, asthma, allergic rhinitis and actinic keratosis . Bagel et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TSQM‐9 is a reliable instrument to assess patients' satisfaction with treatment. It has been used to assess the treatment satisfaction in various diseases such as pulmonary arterial hypertension, multiple sclerosis, psoriasis vulgaris, diabetes mellitus, asthma, allergic rhinitis and actinic keratosis . Bagel et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to assess the treatment satisfaction in various diseases such as pulmonary arterial hypertension, multiple sclerosis, psoriasis vulgaris, diabetes mellitus, asthma, allergic rhinitis and actinic keratosis. [10][11][12][13][14][15] Bagel et al 12 used the TSQM-9 to evaluate the treatment satisfaction with a topical suspension of calcipotriene and betamethasone dipropionate in patients with psoriasis vulgaris and reported that, at the end of the 8-week treatment, the mean TSQM-9 scores for effectiveness, convenience and global satisfaction domains ranged 68-74. To the best of our knowledge, this is the first study to assess TSQM-9 scores in psoriatic patients who were treated not only with topical drugs but also systemic treatments including biologics.…”
Section: Discussionmentioning
confidence: 99%
“…The TSQM‐9 focuses specifically on the three domains of Effectiveness, Convenience, and Global Satisfaction . The TSQM‐9 has been used to assess treatment satisfaction for some diseases but has not yet been applied to atopic dermatitis.…”
Section: Tsqm‐9 Correlation Between Global Satisfaction Domain Of Tsqmentioning
confidence: 99%
“…This outcome was mentioned as critically important by 79% of participating experts, and 54% of participating patients considered dosage adherence as critically important. Topical dermatology treatments are often challenging due to prolonged and complex treatment regimens and can often lead to treatment nonadherence [ 19 , 20 ]. Therefore, efforts to maximize treatment compliance should be encouraged [ 19 ].…”
Section: Discussionmentioning
confidence: 99%